Mobility investigation of a designed and developed segmented rubber track vehicle on Sepang peat terrain in Malaysia - Rahman, Mohammed Ataur; Yahya, Azmi; Mohiuddin, A. K. M. (Professional Engineering Publishing, 2007)
The traction mechanics of a vehicle was developed based on the track–terrain interaction mechanism. The vehicle was tested on three different terrains: terrain I, terrain II, and terrain III. The tractive effort of the vehicle increased 14 per cent when the moisture content of the terrain increased from 59.85 per cent to 81.06 per cent. A traction coefficient of 48 per cent of the vehicle’s gross weight justified the vehicle’s optimum design for the Sepang peat terrain. Less variability of the vehicle’s tractive effort for straight motion in the range of 7.5 per cent to 13.2 per cent and for turning motion in the range of 9 per cent to 11.5 per cent between the predicted and measured tractive effort on the peat terrain III for different loading and operating speeds substantiate the validity of the developed mathematical model.